Tolerance of some Rhizobium leguminosae bv. Vicia strains to different salt concentrations - Shoaib, Faraj Mohammed; Vitouri, Mikael Youssef; Attia Allah, Edriss Hamad (Al-Mukhtar Journal of Sciences, 2009)
The aim of the present study was to determine the tolerance of Rhizobium leguminosarum bv Vida isolates to different concentrations of salinity stress To achieve this aim, three strains were isolated from faba bean grown on different soil types of Al-Jabal A1 Akhdar eco-region. Bacterial growth, in yeast mannitol broth, was obtained at different levels of salt stress by measuring the turbidity at 600 nm. Results revealed that, some variations were observed in bacterial response to different salt stress and it was attributed to the direct and indirect effects of salt stress. Differences in response to salinity refer to the adaptation of the strains to tolerate the increased salinity stress. At high salinity levels, the detrimental effects were also observed.